Floral Art Design: Potensi Kewirausahaan di Desa Wisata Gunung Salak, Tabanan, Bali - Ida Ayu Sri Puspa Adi; I Gusti Ayu Putu Wita Indrayani; Ni Ketut Iswarini; Putu Gede Eka Darmaputra (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2021)
This article aims to discuss the implementation of Community Service activities in Gunung Salak Tourism Village, Tabanan, Bali with the topic: floral art design. The activity was carried out for one full day on April 7, 2021 at Banjar Kemetug with participants mostly from young people. This training activity was carried out using demonstration, question and answer, and working in groups. The results showed that this activity increased the insight and knowledge of the participants in Gunung Salak Tourism Village in utilizing the natural potential in their village and empowering local genius skills possessed in processing coconut leaves. Insights, basic knowledge, and simple flower arrangement skills taught by the facilitators are expected to be developed into entrepreneurial ventures for the village community because they have good business prospects at this time.